Eli Lilly and Beyond The Role of International Intellectual Property Treaties in Establishing Legitimate Expectations in Investor-State Dispute Settlement - Stepanov, Ivan (Munich Intellectual Property Law Center - MIPLC, 2018)
Through the emergence of several high-profile investment arbitration cases, the effects of IPRs as investments covered under IIAs have finally come to light. The latest award, the only arbitration case dealing with patents as IPRs - the Eli Lilly v. Canada case - has brought up a number of interesting questions. Two of Eli Lilly's patents have been revoked, whereupon the company tried to redeem them through investment arbitration. One of the claims put forward by Eli Lilly is that his legitimate expectations, a standard of protection found in international investment law, have been frustrated by Canada. By allegedly failing to observe its obligations contained in Chapter 17 of the NAFTA, Canada frustrated the legitimate expectations of Eli Lilly. The thesis tries to analyze how the relationship between international IP treaties and legitimate expectations functions.